Imposed Change During Merger: Impact on Psychological Contract of employees - Mysore, Somashekar Sthaneshwar (2008)
Acquisitions, amalgamation or mergers and change have been an ongoing part of the operational strategy of many organisations with the intention of achieving growth or rationalisation (Cartwright & cooper, 1992). Kavanagh and Ashkanasy (2006) have noted that amalgamation or mergers are highly complex events with a number of factors that can lead to success or failure and because they influence so many parts of the participating organisations in such fundamental ways. As such, amalgamation, mergers and acquisitions represent sudden and major change and generate a great deal of uncertainty (Davy, J. A., A. Kinicki, J. Kilroy and C. Scheck; 1988). How change occurs within organisations will be influenced by the fact that cultures in the merging organisations are underpinned by deep assumptions that are patterned and shared Schein, E. H. (1992). Sathe,V. and Davidson E. J. (2000). suggest that that culture change consists of changing people’s minds as well as their behaviour. The manner in which the culture change for each individual is evoked also has a significant impact on the result and the consequences for each individual and the implicit reciprocal promises and obligations that they perceive exists with the organisation or in other term the psychological contract. A key factor in any move to shape processes and culture, to build cohesiveness or to develop and promote shared values, must lie in the sense-making processes of the individuals affected during change (Weick, K. 1995). While experts have stipulated various approaches to prepare an organisation and the individuals to successfully undergo transformation and to adapt new behaviours and attitudes desired by the organisation, mergers where rapid changes are injected with a top down approach do not follow the suggested approach to managing change. This study being undertaken is to understand and uncover issues that surface during a merger activity of two very different organisations with regards to size, structure and culture where change is being imposed on the less dominant organisation. The study will focus on the role of leaders and their style of leadership, role of communication while change is being injected, issues arising due to rapidly changing organisation structure & culture and most importantly the effect these factors could have on the individuals in the organisation and their perceived psychological contract. The study is specific to the context wherein a Government-linked company (GLC) of Malaysia has acquired another Malaysian company which is privately owned and the two are being merged.